Determinants of household-level food and nutritional security in urban vegetable producers: A case study - Yusuf UMER; Petros CHAVULA; Mohammed ABDUMALIK; Abdisha Abrahim ADAME; Selahdin AHMED; Eliyas ABDI (Nova Geodesia)
As the world population keeps growing, the demand for food and nutrition security is increasing; requiring sustainable practices that boost food production with environmental preservation is a current world issue. Hence, determining the factors influencing the household food and nutrition security of urban vegetable producers in Chelenko and Kullubi cities in the East Hararghe Zone, Ethiopia, was carried out in this study The research collected information from both primary and secondary data sources. A random sampling technique was used to collect primary data from 232 sampled household respondents. As a result, the data was analyzed using binary logistic and ordered logit models to determine the factors influencing household food and nutrition security, respectively. The descriptive statistics result revealed that 45.69% of households are food secure and the rest 54.31% are food insecure. Similarly, it was found that 40.09%, 33.19%, and 26.72% of the total sample households were in the low, medium, and high nutritional status categories, respectively. The results from the estimated coefficients of the binary logit model revealed that the households with factors such as the sex of household head, cultivated land size, total livestock owned, access extension service, more farming experience, participation in training, and membership in a cooperative were more likely to be food secure. The result of the estimated coefficients of the ordered logit regression model showed that the sex of the household head, cultivated land size, total livestock, extension service, access to credit, off-farm activity, and income have a significant influence on the household-level nutrition security status. While the large family size and dependent ratios were negatively associated with food and nutrition security status. Thus, policymakers should consider the above-mentioned variables to increase agricultural productivity to improve their food and nutrition security status.